x(x - 17)(x - 1)
Factorising x3 - 18x2 + 17x:
Common factor x of all terms:
x(x2 - 18x + 17)
17 = -1 x -17, -1 + -17 = -18:
x(x - 1)(x - 17)
Chat with our AI personalities
(x+1)(x+5)(x+2)
x3 + x2 - 17x + 15 = (x - 1)(x - 3)(x + 5). Thus, the zeros are 1, 3, and -5. All three zeros are rational.
18x2 + 15x + 2 = (3x + 2)(6x + 1)
3x2 + 17x + c = 0, rearranging gives c = -3x2 - 17x
108x2-102x+24 Simplified by dividing all terms by 6: 18x2-17x+4 When factorised: (9x-4)(2x-1) With a question like this using the quadratic equation formula will help.